Pengembangan Lembar Kerja Siswa Eksploratif Berkonteks Budaya Banten pada Mata Pelajaran Matematika di Sekolah Dasar - Lestari, Hana; Pamungkas, Aan Subhan; Alamsyah, Trian Pamungkas (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
Development of Exploratory Student Worksheets Based on Banten Cultural Context in Mathematics Subjects in Elementary Schools. The purpose of this research to describe the development and feasibility process of the student worksheets based on Bantenese culture, to know the studentâ€™s understanding after using student worksheet in the topic of geometry especially volume. This research is the research and development (RnD) using 4-D models (Define, Design, Development, and Dissemination). The subject of this research was the fifth-grade students of SDN Serang 3 consist of 20 students. The data in this study were collected using the questionnaire and test. Based on the results of this research obtained a score with a percentage from content experts 84.16% with very feasible categories, from media experts 85.83% with very feasible categories, 79.99% from linguists expert with feasible categories, 99.33% from user responses with very good categories and 86.75% the test results with very good categories. The results of this research indicate that the product can be interpreted to be effective in increasing students’ understanding of the geometry topic, especially volume.